Conflict Resolution in Tobelo North Halmahera - Nur, Abubakar Muhammad; Titaley, Elsina (Universitas Negeri Padang, 2025)
Conflicts and religious (Islamic and Christian) violence within the Hibua Lamo Halmahera Utara community can not be solved by religious leaders' approaches, whereas in many cases, religious conflicts can be resolved through religious leaders' approaches. Conflict resolution in the Hibua Lamo community is an attempt to analyze and solve problems, considering cultural values. This study uses qualitative methods to describe and analyze conflict resolution technology in the Hibua Lamo community. Data collection techniques are done through observation, interview, and documentation. The results show that the first resolution of conflict and the realization of social cohesion within the Hibua Lamo community, due to the immediate awareness of the community played by the local elite, with the approach of traditional leaders to return to nature as indigenous people immediately. Secondly, Hein Namotemo (traditional leader), acting as a locomotive of conflict resolution, escorted himself to two powers, the Regent of North Halmahera and